Germany in a new era - Geipel, Gary L. Hrsg (Hudson Inst, 1993)
Putting Germany back together again : the great social experiment of unification / David P. Conradt -- The nature and limits of German power / Gary L. Geipel -- The integration of a unified Germany : update and outlook / Gerald R. Kleinfeld -- Forces and legacies shaping a new Germany / Gregory F. Treverton -- United Germany in a uniting Europe / Edwina S. Campbell -- The future role of a united Germany in the European community / Karl H. Cerny -- New bargains : Germany as Europe's central power / Daniel Hamilton -- The future of German strategic thinking / Ronald D. Asmus -- Unified Germany : a great power with many options / Jeffrey T. Bergner -- A special kind of superpower? Germany and the demilitarization of post-Cold War international security / Clay Clemens -- Reconsidering economic masochism in Germany / Alan Reynolds -- The global economic effects of German unification / W.R. Smyser -- Unification and beyond : a chronology / compiled by Christopher J. Spahr